The Effect Of Aqueous Extract Of Anastatica Hierochuntica On Some Hormones In Mouse Females - Baker, Rajaa K.; Mohammd, Tagreed U.; Ali, Bushra H.; Jameel, Nibras M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Anastatica hierochuntica is believed to be very useful in Arab countries for treating various health disorders. The aqueous extract of Anastatica hierochuntica was investigated for its effects on hormones in mice females. the aqueous extract of plant at a dose level of 100mg/1mL showed significant increase (p<0.05) on levels of hormones LH, FSH, PRL level and PRO level. Clomid treated group showd significant increase in LH, FSH, and PRL while there was non-significant increase in PRO. From the above results, it is concluded for the first time that aqueous Anastatica hierchuntica extract offers significant effect of LH, FSH, PRL, and PRO in this mice females scompared with control.